The Effectiveness Of Sabo Dam Modular As A Clean Water Intake Weir (Case Study Of Work For Huntap Tondo Raw Water Project) In Palu City, Central Sulawesi - Prasetyo, Eko; Yulianti, Erni; Dewi, Grace Citra (Publikasi Indonesia, 2023)
This research discusses the topography and geology of Palu City, Central Sulawesi, as well as the condition of the land around the